Peningkatan Kapasitas Masyarakat Melalui Kegiatan Pelatihan Penyulingan Minyak Serai Wangi - Fitria Dewi Kusuma; Zidan Mawla; Ismi Arsilah Rahmawati; Khoirul Nangim; Yoga Widiantoro Pamungkas; Tejo Arum; Maulidia Shufwatul Mala; Salimah; Muhammad Akmal Rizqullah; Agmi Sinta Putri (Altifani Journal: International Journal of Community Engagement, 2025)
Citronella is an essential oil commodity plant with enormous potential for development. The citronella Farmers Group, which includes members from Makroman Village, Sambutan District, Samarinda City, and Sidomulyo Village, Anggana District, Kutai Kartanegara Regency, has citronella land that has not yet been processed into products. Among the products offered through this community service activity is essential oil. By taking an approach that focuses on enhancing community capacity, it is hoped that the training will motivate the development of citronella-based products. This activity includes training, practice, and evaluation. The training provided citronella. During the community practice activity, they directly practiced operating the distillation equipment to obtain essential oils. The activity evaluation was conducted to assess the participants' level of understanding through pre-tests and post-tests. The training activity proved effective based on the evaluation results, which showed improvements in the affective, cognitive, and psychomotor domains. This activity contributes to increasing public knowledge and has the potential for sustainable mentoring.